Excessive sleepiness of Thai night shift workers in medical circumstances indexed by Epworth Sleepiness Scale - Phucharoen, Phuttharaksa; Sittiprapaporn, Phakkharawat (Asian Journal of Medical Sciences, 2019)
Background: Excessive sleepiness is a cardinal symptom of many sleep disorders including shift work sleep disorder. As shift work sleep disorder is one type of the circadian rhythms sleep–wake disorders (CRSDs), it composes of symptoms of insomnia or excessive sleepiness associated with a recurring work schedule that intersections with the usual sleep timetable. Aims and Objective: The objective was to study the sleep propensity (SPs) in Thai medical staffs who are working in the hospital in Thailand. Materials and Methods: Ten participants included night shift workers with excessive sleepiness. Each participant was assessed by standardized measures of excessive sleepiness (Epworth sleepiness scale [ESS] ≥ 11). Exclusions included clinical major medical problem, psychiatric, neurological problem, use of drugs other than alcohol, uncorrected serious vision issue, pregnancy and lactation, use of antibiotics and herbs during this study. The ESS item scores in this study are all assessments of different situational SPs. Results: The results showed that about 70% of the subjects answered slight chance of dozing, while 20% answered moderate chance of dozing for sitting and reading situation. Only 10% of the subjects would never doze. There were 60% of the subjects answered slight chance of dozing, while 10% answered moderate chance of dozing for as a passenger in a car for hour without a break of the ESS. There were 30% mentioned that they would never doze. Conclusion: The situations can be described in general terms but not completely, for they depend on the subject’s perception of them. Although these preliminary findings represent a relatively information, it may not reflect all the SPs in Thai medical staffs who are working in hospital. It need further research to be done in the larger extended way.